Implementation of computer simulation in rubber assembly line: a case study (Rubber Research Institute Of Malaysia) - Mohamad Amran, Mohd. Fahmi (2006)
Simulation is one of the modeling techniques in solving industrial problem that can imitate the real system through model development. In Rubber Research Institute of Malaysia (RRIM), assembly line of Deproteinised Natural Rubber (DPNR) that has been operating since 1994 had never been modeled through simulation method in improving and solving the production problem. Therefore, the implementation of computer simulation in the DPNR assembly line at RRIM is appropriate to solve two main problems namely increasing production capacity, and ineffective production line. In order to achieve the objective, facilities layout, automating the process of assembly line and increase the conveyor speeds were proposed as a method to improve the current system. In this project, the simulation modeling was applied discrete event simulation and the flow manufacturing simulation as a methodology. The simulation model was developed and tested using ProModel 6.0 Network Version software. The data analysis was carried out using Stat::Fit of ProModel software. Data was collected and evaluated to determine the necessary parameters that are used in the simulation model. This project is wished to be implemented as solutions to the problem faced by the current system